There Is No Such Thing as Zero Risk of Sexual Offending - Lee, Seung C. (Canadian journal of criminology and criminal justice, 2023)
The public is justifiably concerned about the risk presented by individuals with a history of sexual crime. Given that recidivism risk varies across individuals and over time, what level is so low as to be indistinguishable from sexual recidivism risk in the general population (a desistance threshold)? This risk is not zero. Comparing census data with the number of males convicted of sexual offences in the province of British Columbia in two cohorts (2006, N = 362; 2011, N = 422), we found that approximately 1% of all adult males in British Columbia would be expected to be convicted of a sexual offence by age 50. Across the full lifespan (until 99), that proportion was estimated to be 1.38% for the 2006 cohort and 1.50% for the 2011 cohort. Other research has found that most individuals released from a sexual offence present a similarly low residual risk (< 2%) after 10 years of being offence-free in the community. Consequently, applying long-term restrictions (e.g., lifetime registration; Criminal Code of Canada §161) to such individuals serves no public protection function.